Mapping the film and audiovisual sectors : a research agenda for the future - Damásio, Manuel José (2022)
The film and audiovisual sectors plays a key role in European society, and by extension also in Portugal. In this paper we propose a conceptual change centered on mapping the film and audiovisual (AV) industries in Portugal as a creative sector, instead of a cultural one. We argue that this enables a more rigorous measurement of the value of these industries in the creative economy, besides allowing for easier connections between the creative industries and other areas. This conceptual change is based on an innovative approach to the “creative trident”. We argue that the value of the film and AV sector has to be rooted in a flourishing creative workforce, and we propose that entrepreneurship education can be a path forward in unlocking the sector tremendous creative potential. We propose an innovative research agenda to deal with linking all these elements in the context of the audiovisual and film creative industries. keywords: mapping studies; creative industries; cultural industries; creative professions; creative trident; entrepreneurial education; creative workforce; creative skills